EFEK APLIKASI SERICIN PADA HIDROKSIAPATIT TERHADAP PERLEKATAN SEL OSTEOBLAS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Hydroxyapatite (HA) is often used as a human bone grai Modification of HA surface is developed to increase osseointegration process which is influenced by cells attachment surrounded the tissue. Sericin has polar side groups which acceleratecells attachment. The aim of this researchwas to determine the effectof sericin application over HA surface on the attachment of osteoblast cells. The research used HA synthesizedfrom gypsum (Kulon Progo, Yogyakarta). Sericin was extracted from silkworm cocoonsof Bombyx mori. Sericin of 0.01, 0.05, 0.1% were applied over HA discs surface (10 mm in diameter, 3 mm thick). The discs were inserted into osteoblastcells culture of MC3T3El for attachment test. The data were analyzed by ANOV A and LSD. The result showed that the amount of osteoblast cells attached to HA (7.60I0.42) was significantly difference (p0.05). In conclusion, sericin application over HA surface increased the amount of osteoblast cells attachment. Concentrations of sericin application over HA (0.01, 0.05, 0.1%) did not influence osteoblastcells attachment.